The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-2842.2006.01702.x
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of direct composite restorations for the worn mandibular anterior dentition – clinical performance and patient satisfaction

Abstract: This prospective split-mouth clinical trial evaluated the performance and patient satisfaction of 168 Herculite XRV direct composite restorations bonded to the worn anterior dentition of 18 patients with localized anterior tooth surface loss. One hundred and six of these restorations were placed on the mandibular anterior teeth. The restorations increased the anterior occlusal vertical dimension between 0.5 and 5 mm and the posterior occlusal contacts were restored after a mean duration of 6.2 months (range: 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
80
0
16

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(106 citation statements)
references
References 15 publications
3
80
0
16
Order By: Relevance
“…Several studies in the literature since have reported success in achieving the desired relative axial tooth movement using the Dahl principle, ranging from 93% to 100% of all cases. [7][8][9][10][11] The science and technology of composite dental restorative materials have advanced considerably over the years. Although composites have not evolved to the point of being an ideal restorative material, they have become a viable option to manage localised anterior tooth wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the literature since have reported success in achieving the desired relative axial tooth movement using the Dahl principle, ranging from 93% to 100% of all cases. [7][8][9][10][11] The science and technology of composite dental restorative materials have advanced considerably over the years. Although composites have not evolved to the point of being an ideal restorative material, they have become a viable option to manage localised anterior tooth wear.…”
Section: Introductionmentioning
confidence: 99%
“…The successful use of composite resin restorations placed at an increased occlusal vertical dimension as 'Dahl' type appliances has been demonstrated over the short-term. [7][8][9][10][11][12] This simple technique offers better patient compliance compared…”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65] Long-term follow-up studies show that the main complications are repairable and retrievable with no loss of tooth vitality or need for loss of further teeth. 63 It has been reported that chipping or partial debonding may appear in teeth with no, or minimal, enamel at the margins of the worn surfaces, but the majority of problems are restorable.…”
Section: Longevity and Maintenancementioning
confidence: 99%
“…Diante do seu rápido aperfeiçoamento, combinado com o uso dos sistemas adesivos, a resina composta hoje em dia é utilizada na maioria das restaurações estéticas diretas em dentes anteriores 3,8 , solucionando um número cada vez maior de situações clínicas de alterações de função, forma e estética [8][9][10] , sob um conceito de intervenção operatória minimamente invasiva 11 . Contudo, o profissional deve conhecer os limites do material para oferecer e optar pelo melhor tratamento diante desses casos de reabilitação.…”
Section: Introductionunclassified